Looking for the road: the pedagogical supervision in music teacher education - Cardoso, Mário (2020)
The pedagogical supervision has always deserved the attention and interest of many researchers. The analytical and reflective approach that is presented aims to discuss, in addition to the different places of supervision, what readings of the supervisory function are dominant in the teacher training in music education. Faced with the lack of systematized knowledge in this context, this study was developed with a socio-constructivist and ecological matrix with the general purpose of reflecting on the supervision and the specificities of its practices in the particular context of music teacher education. Based on a convenience sample, the study is part of a qualitative, descriptive and interpretive approach, in which one seeks to know the professional learning achieved during supervised teaching practice. Considering the general aim of this research, the reflexive reports of the practicum, constructed based on the experience and meaning of the daily practices in musical education rooms are described, analysed and interpreted. The data of the reports are interspersed with the information provided by the monitoring carried out by the supervisors, reflective portfolios and with the theoretical framework. Discursive textual analysis of the reports was guided by the identification of: (1) the challenges and achievements of trainees in the learning of practical professional skills; (2) the recognition of portfolio as an instrument for reflection of the individual learning journey during supervised teaching practice; (3) supervision strategies in the processes of involvement and transformation of trainees during their supervised teaching practice. The analysis of the data reveals: (1) the challenge is on the processes and performance of everyday work experience (learning to know, learning to do, learning to be); (2) incentive to self-questioning, self-evaluation, self-training and experimentation; (3) an effort is made to overcome instrumental and technical perspectives; (4) reflection becomes a potential factor in the development of fundamental attitudes and necessary to the profession, self-understanding, the construction of pedagogical knowledges and the understandings manifested in the course of this trajectory; (5) the relation and dialogue with the literature during the process of teacher construction is fundamental and necessary to overcome the challenges that the educational context places on a daily basis and to consolidate the different conceptual lines studied throughout the training; (6) supervisory relation relationship is marked by a predominantly collaborative style; and (7) the reflective portfolios is an effective possibility of making visible the invisible (the teacher thinking in his (de)construction process).